“I felt sad then, I feel free now”: a case for examining the constructive resistance of opted-out mothers - Yoong, Melissa; Mohamed, Nourhan (Emerald, 2023)
Purpose While past research has explored how opting-out enables mothers to break free from masculinist organizational cultures, less attention has been given to how they resist disciplinary power that constitutes and governs their subjectivities. This paper aims to add to the discussion of opting-out as a site of power and resistance by proposing the concept of “constructive resistance” as a productive vantage point for investigating opted-out mothers' subversive practices of self-making.